Unintended Sunburn: A Potential Target for Sun Protection Messages - Geraldine F. H. McLeod; Anthony I. Reeder; Andrew R. Gray; Rob McGee (Journal of Skin Cancer)
New Zealand (NZ) has the highest melanoma incidence rate in the world. Primary prevention efforts focus on reducing sunburn incidence and increasing sun protective practices in the population. However, sunburn from excessive ultraviolet radiation (UVR) remains common. To reduce sunburn incidence, it is important to examine those individuals who experience unintended sunburn. This study aims to use data from the NZ Triennial Sun Protection Survey to describe respondents who were not intending to tan but were sunburnt after outdoor UVR exposure. Information on sociodemographics, concurrent weather conditions, sun protection attitudes and knowledge, and outdoor behaviour was also collected. The results showed 13.5% of respondents’ experienced unintended sunburn during the survey weekend but had not attempted to obtain a tan that summer. Respondents who reported unintended sunburn were more likely than others to have been near water and in unshaded areas, used sunscreen, had higher SunSmart knowledge scores, had lower positive attitudes towards tanning, and were outdoors for a longer duration with less body coverage. As sunburn was unintended these respondents’ outdoor sun protective behaviours may be amenable to change. Future public health initiatives should focus on increasing sun protection (clothing and shade) and reducing potential barriers to sun protection.